2014
DOI: 10.1038/jp.2014.4
|View full text |Cite
|
Sign up to set email alerts
|

Super obesity in pregnancy: difficulties in clinical management

Abstract: As the obesity pandemic continues in the United States, obesity in pregnancy has become an area of interest. Many studies focus on women with body mass index (BMI) ⩾ 30 kg m(-2). Unfortunately, the prevalence of patients with BMI ⩾ 50 kg m(-2) is rapidly increasing, and there are few studies specifically looking at pregnant women in this extreme category. The purpose of this article is to highlight some of the challenges faced and review the literature available to help guide obstetricians who might encounter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Maternal obesity may be an independent risk factor for CS as it interferes with the progress of labour, specifically the arrest of dilation in active phase labour [ 13 ]. The higher rate of CS has been explained in other studies by the association of super-obesity with conditions such as gestational diabetes, gestational hypertension and preeclampsia [ 14 16 ], all of which were more prevalent in women in our study. This is consistent with other research including comparison with other obese women (BMI 30.0–49.9 kg/m 2 ) [ 5 ].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Maternal obesity may be an independent risk factor for CS as it interferes with the progress of labour, specifically the arrest of dilation in active phase labour [ 13 ]. The higher rate of CS has been explained in other studies by the association of super-obesity with conditions such as gestational diabetes, gestational hypertension and preeclampsia [ 14 16 ], all of which were more prevalent in women in our study. This is consistent with other research including comparison with other obese women (BMI 30.0–49.9 kg/m 2 ) [ 5 ].…”
Section: Discussionsupporting
confidence: 67%
“…Hospital guidelines and other recommendations would suggest thromboprophylaxis for women in the study group who had caesarean sections is warranted. There is, however, little or no differentiation of risk according to degree of obesity [ 19 – 21 ]; although Martin et al highlights the dose–response of increased risk of thromboembolic events and eclampsia as BMI increases and suggests this can be usefully applied to other pregnancy-related complications [ 16 ]. This amplified risk of morbidity according to BMI is consistent with the Mbah study discussed earlier and showed a significantly increased risk of pre-eclampsia between super-obese women (BMI ≥ 50 kg/m 2 adjusted odds ratio 4.71 [4.20–5.28]) compared to women with Class III obesity (3.75 [3.59–3.92] [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 80% of our cohort was obese and African American. The obesity epidemic in the United States continues, and this is especially prominent in the South and among African American women . The possibility of an LFF result may also increase with this growing epidemic, and providers are encouraged to discuss the possibility of an LFF result, in particular with obese African American women.…”
Section: Discussionmentioning
confidence: 99%
“…HPs felt that caring for obese women required more time and work in a setting with limited resources, a theme similar to challenges identified in maternity settings 18 and reflective of additional considerations required for providing their maternity care. 19 HPs also felt obese women were more difficult to care for because of their complex medical issues and difficulties with finding successful breastfeeding positions. The combination of an obese woman's concern for exposing her body, general exhaustion, and a difficult postpartum course posed more challenges.…”
mentioning
confidence: 99%